Evaluación de la factibilidad técnico-financiera del Plan de Desarrollo de un campo en la Cuenca de los Llanos Orientales mediante la creación de un modelo de Simulación de Yacimiento (2019)
This dissertation describes the characterization of a reservoir for a field located in Llanos Orientales Basin by creating a dynamic model of numerical simulation. To do this, a static model building had to start. It allowed to model the combined trap that generated the reservoir and that consists of the lateral pinch-out of the reservoir unit against the basement that is uplifted there due to tectonic stresses that define the monoclinal structure of the area where the field is located. The presence of faults is not relevant, and the closure of the reservoir is determined by the presence of the basement and the oil-water contact. The assignment of model properties was realized for each rock type parting from a lithological and petrophysical characterization based on compositional and textural variations that control porosity and permeability inside the rock. Fluid flow characteristics and their interaction with rocks were recreated using the numerical simulation model. It was posible to evaluate the scheme or well architecture proposed on the Field Development Plan, and it was also possible to compare it with an optimized scheme by using this tool. Thus, after a financial evaluation, it was posible to choose the architecture that best fits the reservoir characteristics.